2019
DOI: 10.4070/kcj.2019.0180
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Potential of an SGLT2 Inhibitor Against Doxorubicin-Induced Heart Failure

Abstract: Background and ObjectivesRecent studies have shown that sodium-glucose co-transporter 2 (SGLT2) inhibitors reduce the risk of heart failure (HF)-associated hospitalization and mortality in patients with diabetes. However, it is not clear whether SGLT2 inhibitors have a cardiovascular benefit in patients without diabetes. We aimed to determine whether empagliflozin (EMPA), an SGLT2 inhibitor, has a protective role in HF without diabetes.MethodsCardiomyopathy was induced in C57BL/6J mice using intraperitoneal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
(28 reference statements)
6
44
0
Order By: Relevance
“…The significant reductions of cardiovascular events with SGLT2I's could not be attributed solely to their glucose lowering effects. SGLT2 inhibitor (EMPA) had a protective effect in Dox-induced HF in mice as manifested by improved heart function and reduced fibrosis [21]. In the Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The significant reductions of cardiovascular events with SGLT2I's could not be attributed solely to their glucose lowering effects. SGLT2 inhibitor (EMPA) had a protective effect in Dox-induced HF in mice as manifested by improved heart function and reduced fibrosis [21]. In the Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Different SGLT2 inhibitors have moreover been shown to activate AMPK in cardiofibroblasts [168] and adipocytes [169]. Two recent studies furthermore showed that SGLT2 inhibitors preserve heart function in mice [170] and rats [171] treated with DOX. Another antidiabetic drug, liraglutide, a glucagon-like peptide-1 (GLP1) analogue, protected rats from DOX-induced inflammation and necrosis by activating AMPK and the Akt signalling pathway [90].…”
Section: Ampk Activation By Other Compoundsmentioning
confidence: 99%
“…In addition, more recently, sodium-glucose co-transporter 2 (SGLT2) inhibitors, a new class of antidiabetic agents that improve glycaemic control, were shown to reduce the risk of heart failure-associated hospitalization and mortality in patients with diabetes. Interestingly, it was demonstrated that SGLT2 inhibitors attenuated DOXO-induced cardiotoxicity in mice [154]. This protective effect was mediated by elevated beta-hydroxybutyrate levels, which reduced ROS production and improved mitochondrial dysfunction in cardiomyocytes.…”
Section: Diabetes and In Cancer And Cardiovascular Diseases Cardiotoxmentioning
confidence: 99%